Family life education in India : perspectives, challenges, and applications - Chowdhury, Aparajita, 1958-; Carson, David K.; Carson, Cecyle K. (Jaipur : Rawat Publications, 2006)
Contributed articles.
Includes bibliographical references (p. 317-321) and index.
Keywords: Family life education -- India